Analysis of Contract Farming Partnership for Sustainable Supply of Tobacco (a Case Study on the Integrated Production System Program of PT. HM Sampoerna Tbk. - Indonesia) - DS Susilowati, Kartika; Rachmi, Asminah; Indah Riwajanti, Nur (International Journal of Engineering and Technology, 2018)
This study explored the implementation of the integrated production system program established by PT. HM Sampoerna Tbk Indonesia, a leading Indonesian tobacco company, and examined its potential and constraints. The program was intended to develop cooperation between the company and its tobacco suppliers to get a sustainable supply of tobacco from farmers with quantity, quality and price set according to the company’s standards. This study employed an interpretive research design, following a post-positivist paradigm. The data were collected by means of in-depth interviews, observation and document study and were analyzed using the key tenet of Martin Heidegger’s interpretive phenomenology. The interpretive process was achieved through hermeneutic circle to understand how individuals involved in the program interpreted the program including their own experiences as well as their interactions with other parties. The results of the study indicated that the created contract farming partnership was capable of providing the company with a sustainable supply of tobacco and increasing its production volume. Nevertheless, it was unable to improve the quality of the farmers’ lives as it was chiefly intended to meet the company’s commercial needs. The results from the study have direct relevance to policy makers in Indonesia, especially those that have been implemented contract farming and to agribusiness companies seeking contractual relationships for commodity production.